THE EFFECT OF FREE CASH FLOW AND PROFITABILITY ON DIVIDEND PAYOUT RATIO (CASE OF LQ-45 INDEXED FIRMS IN INDONESIA STOCK EXCHANGE FOR PERIOD 2011-2018) - Lohonauman, Hans; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2021)
This study aims to determine the effect of free cash flow and profitability on dividend payout ratio at LQ45 Index Companies Listed on the Indonesian Stock Exchange 2011-2018. The population used in this study is the LQ45 index company listed on the Indonesian Stock Exchange in 2011-2018. The sampling method was purposive sampling according to predetermined criteria. The number of samples collected was 7 companies. The research data is secondary data obtained from the Indonesian Stock Exchange (IDX) in 2011-2018. The data that has been collected is analyzed using data analysis that first tested with classical assumptions before testing the hypothesis. Hypothesis testing in this study uses multiple linear regression analysis with the t test, f test, and the coefficient of determination. The result of this study indicates that free cash flow does not affect the level of dividend payout ratio. While profitability has a significant effect on dividend payout ratio. This shows that profitability affect the level of dividend payout ratio.